A novel use of high density SNP assays to optimize choice of different crossbred dairy cattle genotypes in smallholder systems in East Africa - Ojango, Julie M.K.; Marete, A.; Mujibi, F.D.N.; Rao, E.J.O.; Poole, Elizabeth J.; Rege, J.E.O.; Gondro, C.; Weerasinghe, W.M.S.P.; Gibson, John P.; Okeyo Mwai, Ally (American Society of Animal Science, 2014)
We present use of SNP technologies to obtain for the first time, rapid, large-scale, in situ estimates of performance of crossbred cows in smallholder herds. Compared to historical approaches, our approach allowed optimum crossbreed choices to be determined more rapidly and without question about the relevance of the environment. High-density SNP assays were used to estimate breed composition for a monitored population comprising 1292 cows from 610 smallholder farms in Kenya. The achieved milk yields are much lower than generally assumed and lactation curves are very flat out to 400 days. In poor production environments, lower grade crosses (containing <60% exotic dairy alleles) had the same yield as high grade crosses. Allowing for the larger size and maintenance requirements of high grade exotics, lower grade exotics will be the most economically productive animals in these environments.